Математичне моделювання демографічних процесів в Україні за допомогою матриць Леслі - Караєв, Е. А.; Жила, О. В. (ХНУРЕ, 2025)
The paper considers an important aspect of Ukraine's economic development, namely the dynamics of the demographic situation in the country on the basis of real statistical data. To model and evaluate this process, the paper uses a classical model of population dynamics based on Leslie matrices. Mathematical and simulation modelling is implemented in the Maple symbolic computing software package. The result of this work is the obtaining of population dynamics by three age groups and visualization of statistical data.
Keywords: матриця Леслі; моделювання демографічних процесів